On a nonlinear system of Biot–Forchheimer type. Issue 12 (1st December 2020) - Atik, Y.; Kabir, H.; Vallet, G.
Abstract : We analyse a nonlinear parabolic/elliptic system describing the high-velocity flow of a fluid in a poro-elastic medium. Based on a time discretization of the parabolic equation and monotone arguments, we prove a result of well-posedness of the problem in the sense of Hadamard. In addition, the strong convergence of the sequence of approximations is proved.